Cultural Continuity and Change: A Study of the Sixteen Samskaras in Modern Hindu Society - Maru, Ronak; Burboz, Criset N. (Integrated Journal for Research in Arts and Humanities, 2024)
This paper explores the cultural continuity and changes surrounding the sixteen samskaras within modern Hindu society. Drawing from a synthesis of scholarly works and classical texts, the study examines the historical significance and contemporary relevance of these rituals. Ramaswami Aiyer, Pandey, and Shelat provide foundational insights into the cultural heritage of India, emphasizing the enduring nature of the samskaras and their role in shaping Hindu identity. Shrutiprakashdas, Dave, Shukla, Vivekpriyadas, and Gnaneshwardas offer philosophical, sociological, and cultural perspectives, elucidating the spiritual dimensions and adaptive qualities of these ceremonies in response to societal shifts. Through an analysis of these sources, this paper seeks to understand how the sixteen samskaras continue to uphold tradition while accommodating changes in modern Hindu society. The Sixteen Samskaras, deeply rooted in Hindu philosophy and tradition, represent a series of sacred rites of passage that mark significant milestones in an individual’s life journey. These rituals, spanning from conception to cremation, play a vital role in shaping the spiritual and cultural identity of Hindus across different regions and communities. Each samskara is imbued with profound meaning and symbolism, reflecting the rich tapestry of beliefs and practices that define Hinduism.